The Centre for Excellence in Teaching (CET) at Portucalense University: goals, strategies and expected outcomes - Fernandes, Sandra (2018)
This paper presents part of the change process carried out at the Portucalense University (UPT), Portugal, aimed at promoting student centred teaching and learning. To attain this goal, the Centre for Excellence in Teaching (CET) was created to support academic staff development, provide pedagogic training for teachers, create pedagogical resources and enhance the dissemination of best practices and teaching quality at UPT. The preliminary results of the implementation of the activities developed by the CET reveal a positive participation and involvement of academic staff, according to data collected through an online questionnaire to participants. Teachers showed interest in developing active learning strategies and openness to change their teaching practices. Some examples of the activities implemented by teachers, in the first semester of 2017/2018, are briefly presented in this paper.